2016
DOI: 10.1038/srep36625
|View full text |Cite
|
Sign up to set email alerts
|

miRNAsong: a web-based tool for generation and testing of miRNA sponge constructs in silico

Abstract: MicroRNA (miRNA) sponges are RNA transcripts containing multiple high-affinity binding sites that associate with and sequester specific miRNAs to prevent them from interacting with their target messenger (m)RNAs. Due to the high specificity of miRNA sponges and strong inhibition of target miRNAs, these molecules have become increasingly applied in miRNA loss-of-function studies. However, improperly designed sponge constructs may sequester off-target miRNAs; thus, it has become increasingly important to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 50 publications
0
56
0
1
Order By: Relevance
“…In this regard, the RNA sponge length may form a short double‐stranded region that influenced the miR‐223 recognition . However, although there is no general rule regarding how many miRNA binding sites should be in a sponge RNA, its functionality would also depend on aspects such as the promoter used, the cell line and the expression of the target miRNA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the RNA sponge length may form a short double‐stranded region that influenced the miR‐223 recognition . However, although there is no general rule regarding how many miRNA binding sites should be in a sponge RNA, its functionality would also depend on aspects such as the promoter used, the cell line and the expression of the target miRNA …”
Section: Discussionmentioning
confidence: 99%
“…17 However, although there is no general rule regarding how many miRNA binding sites should be in a sponge RNA, its functionality would also The normalized signal is expressed as mean ± SD of three independent experiments depend on aspects such as the promoter used, the cell line and the expression of the target miRNA. 18 After demonstrating that the sponge-vector expression pLVX-Sponge-223 4 with four perfectly complementary miR-223 binding sites in tandem did not have an inhibitory capacity for the function of miR-223, we decided to clone the same 60-bp region of the 3'-UTR of human MDR1/ABCB1 mRNA containing an imperfect binding site of miR-223 into the pLVX-shRNA2 backbone. However, the strategy of employing the same backbone to adopt the anti-miR-223 sponge represents a study limitation because this plasmid only expresses a fluorescent protein marker to monitor the transfection efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some tools have been developed, including spongeScan [20], miRNAsong [21], CircInteractome [22], miRNACancerMAP [23], and JAMI [24], to study miRNA sponges. Based on the sequence data of miRNAs and RNA transcripts, the first three web-based tools, spongeScan, miRNAsong and CircInteractome, regard RNA transcripts containing multiple miRNA binding sites as potential miRNA sponges.…”
Section: Discussionmentioning
confidence: 99%
“…Here, a miRNA sponge module is defined as a cluster of miRNA sponges. It has been shown that there is a great potential to reveal the biological mechanisms in cancer by studying miRNA sponge networks and modules [5,11,19], and the computational methods for identifying miRNA sponge networks and modules can help broaden our study of miRNA sponges and generate hypotheses for wet lab experiments.Recently, some tools have been developed, including spongeScan [20], miRNAsong [21], CircInteractome [22], miRNACancerMAP [23], and JAMI [24], to study miRNA sponges. Based on the sequence data of miRNAs and RNA transcripts, the first three web-based tools, spongeScan, miRNAsong and CircInteractome, regard RNA transcripts containing multiple miRNA binding sites as potential miRNA sponges.…”
mentioning
confidence: 99%
“…In the first category [9, 10], similar to miRNA target recognition, the principle of complementary base-pairing is assumed when recognizing miRNA sponges. In other words, it is assumed that there is an interaction between the 5′-end of an miRNA called the ‘seed region’ and the sequence of the miRNA sponge.…”
Section: Introductionmentioning
confidence: 99%